Experimental research on the microclimate in the naturally ventilated multi-span greenhouse - Gao, Zhenjun; Li, Wenyang; Li, Wei; Ding, Xiaoming (International Journal of Agricultural and Biological Engineering, 2024)
In order to further understand the changing laws of environmental factors in large multi-span greenhouses under natural ventilation conditions and the internal relations between various environmental factors, and ultimately improve the precision of microclimate regulation of large multi-span greenhouses. Taking the multi-span greenhouse with a small spire structure in the Demonstration Base of Guangdong Agricultural Technology Extension Station as the research object, under the condition of natural ventilation with butterfly-shaped windows, the changes in temperature, humidity, wind speed and solar light intensity of different monitoring planes in the greenhouse were monitored. After analyzing the monitoring data, it was found that: 1) The temperature gradient in the vertical direction in the large multi-span greenhouse is more obvious than that in the small greenhouse, and the highest average temperature difference monitored can reach 7.9°C. The velocity field in the multi-span greenhouse is always maintained within the range of 0.3-0.4 m/s, and the ambient wind speed has no effect on the airflow speed in the greenhouse. The humidity and speed in the multi-span greenhouse show good uniformity. 2) In a large multi-span greenhouse, the secondary radiation generated by the internal shading has less impact on the area near the ground, which can effectively reduce the ground temperature. 3) Under the conditions studied in this research, the temperature and humidity in the greenhouse follow the external environment as well, showing that the greenhouse design is reasonable, and the air renewal and heat exchange inside and outside the greenhouse are good during natural ventilation. Keywords: natural ventilation, multi-span greenhouse, environmental factors, microclimate DOI: 10.25165/j.ijabe.20241703.7073 Citation: Gao Z J, Li W Y, Li W, Ding X M. Experimental research on the microclimate in the naturally ventilated multi-span greenhouse. Int J Agric & Biol Eng, 2024; 17(3): 68-74.